2014
DOI: 10.1590/1981-8637201400010000032501
|View full text |Cite
|
Sign up to set email alerts
|

Variation of digital palpation pressure used in the clinical examination of TMJ disorders and orofacial pain

Abstract: ObjectiveThe present research aims to evaluate the calibration of digital palpation pressure as well as to assess the inter-examiner variation and mean pressure used by a sample consisting of 56 professionals of the TMJ disorders and Orofacial Pain area. Methods Each 0kg). The t-student test was used to analyze data (p≤0.05). Results 70% of the sample was classified as non-calibrated RESUMO ObjetivoAvaliar a calibração da força de palpação digital, bem como determinar a variação intra-examinador e a força mé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
1
0
3
Order By: Relevance
“…These findings may be further confounded by inconsistent pressure applied between clinicians; as an example, it has been reported that almost 60% of clinicians do not use palpation pressure within the recommended range of 0.8 to 1.2 kg. 28 Hence, other diagnostic tools such as electromyography, 29 histochemistry, 29 thermography, 30 pressure algometry, 30 and magnetic resonance imaging elastography 30,31 have been studied. However, their high cost and limited availability and clinical value hinder their use.…”
mentioning
confidence: 99%
“…These findings may be further confounded by inconsistent pressure applied between clinicians; as an example, it has been reported that almost 60% of clinicians do not use palpation pressure within the recommended range of 0.8 to 1.2 kg. 28 Hence, other diagnostic tools such as electromyography, 29 histochemistry, 29 thermography, 30 pressure algometry, 30 and magnetic resonance imaging elastography 30,31 have been studied. However, their high cost and limited availability and clinical value hinder their use.…”
mentioning
confidence: 99%
“…Para o diagnóstico inicial, foi empregado o RDC/TMD, instrumento que contempla extensa gama de aspectos clínicos, considerado padrão ouro para este tipo de avaliação 63 . Para maior confiabilidade e reprodutibilidade dos dados obtidos, a palpação foi realizada com o auxílio de um algômetro 68 .…”
Section: Methodsunclassified
“…pesquisadores. Lima et al68 , em estudo sobre a variação da pressão incidente na palpação digital, avaliaram 56 profissionais que atuam na especialidade de disfunção…”
unclassified
“…Para o diagnóstico inicial, foi empregado o RDC/TMD, instrumento que contempla grande gama de aspectos clínicos, considerado padrão ouro para este tipo de avaliação (Schiffman et al, 2010). Para maior confiabilidade e reprodutibilidade dos dados obtidos, a palpação foi realizada com o auxílio de um algômetro de pressão (Lima et al, 2014) (Karcioglu et al, 2018). Além disso, para avaliação dos efeitos terapêuticos da TFBM no quadro de disfunção temporomandibular, a EVA é a ferramenta mais utilizada (Xu et al, 2018).…”
Section: Dor Total Direita (D)unclassified